The Frenet-Serret description of Born rigidity and its application to the Dirac equation - Formiga, J.B. (Revista Mexicana de Física, 2020)
The role played by non-inertial frames in physics is one of the most interesting subjects that we can study when dealing with a physical theory. It does not matter whether we are studying classical theories such as special relativity or quantum theory, the idea of an accelerated frame is always one of the first ideas to come to our minds. In the case of special relativity, a problem with the concept of rigidity emerged as soon as Max Born gave a reasonable definition of rigid motion: the Herglotz-Noether theorem imposes a strong restriction on the possible rigid motions. In this paper, the equivalence of this theorem with another one that is formulated with the help of Frenet-Serret formalism is proved, showing the connection between the rigid motion and the curvatures of the observer’s trajectory in spacetime. In addition, the Dirac equation in the Frenet-Serret frame for an arbitrary observer is obtained and applied to the rotating observers. The solution in the rotating frame is given in terms of that of an inertial one.